Anonymous whaling document
Fragmentary document consisting of a letter written from Honolulu, Hawaii, in 1853; two pages of verse, "Going to California"; and a page of journal entries (1853 July 18-25). Names several whaling ships, speaks of sailing for the Okhotsk Sea or Arctic Ocean, and mentions individuals including Clothier Pierce.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Pierce, Clothier, -- 1824-1880.; Whaling; Whaling -- Arctic Ocean; Whaling -- Okhotsk Sea; Whaling ships; California -- Description and travel; Honolulu (Hawaii) -- Description and travel